FINANCIAL PERFORMANCE ANALYSIS THROUGHT VALUE FOR MONEY APPROACH IN THE NATIONAL AND POLITICAL UNIT AGENCY OF MAGETAN REGENCY - Kudhori, Ahmad; Hardyanti, Indwi Sinar (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2022)
This study aims to analyze financial performance through a value for money approach at the National Unity and Political Agency of Magetan Regency. The function of value for money serves as a bridge for local governments to achieve good governance. There are main elements as parameters, namely economy, efficiency, and effectiveness. This study uses descriptive analysis method with primary data sources from performance reports and budget realization reports for the National Unity and Political Affairs Agency of Nganjuk Regency, with data collection techniques in the form of interviews with employees who responsible for financial reporting and documentation studies. The results of the study show that the financial performance of the National Unity and Political Agency of Magetan Regency for the 2018-2020 fiscal year viewed from an economic measurement point of view is considered good, with the results of economic measurements being below the criterion figure, which is less than 100%. The results of the economic measurement for the 2018–2020 fiscal year show the numbers 88,90%, 90,16%, and 89,89%, respectively. Judging from the results of the efficiency measurement, the results showed that in 2018 it was 95,67%, in 2019 it was 101,09% and in 2020 it was 90,12%. This shows that in 2018 and 2020 it was categorized as efficient, while in 2019 it was categorized as less efficient. Judging from the results of the effectiveness measurement, 2018 and 2019 were ineffective at 87,61% and 89,15%, while in 2020 it was categorized as effective with a score of 100,12%.